Case Report: Is there an age cutoff beyond which PFO closure should not be offered? - Onorato, Eustaquio Maria; Melotti, Eleonora; Doldi, Marco; Monizzi, Giovanni; Mastrangelo, Angelo; Mallia, Vincenzo; Giacomazzi, Francesca; Andreini, Daniele; Bartorelli, Antonio Luca (Frontiers in Cardiovascular Medicine, 2025)
BackgroundWhile randomized controlled trials have confirmed that patent foramen ovale (PFO) closure over medical therapy is considered the preferred treatment of young patients with embolic stroke of undetermined source (ESUS), the efficacy of percutaneous closure in elderly subjects with high-risk PFO remains unclear since no randomized trials are currently available.Case summaryA 65-year-old man with a past medical history of hyperuricemia, chronic gastroesophageal reflux disease, intestinal diverticulosis, and long-lasting arterial hypertension with enlargement of the aortic root was admitted for evaluation of the sudden onset of diplopia, postural instability, and subtotal loss of consciousness. Brain magnetic resonance imaging (MRI) confirmed an acute left thalamo-mesencephalic infarct. Continuous ECG monitoring ruled out atrial fibrillation (AFib). Two-dimensional (2D) transthoracic/transesophageal echocardiography (TTE/TEE) color Doppler showed a significant right-to-left shunt (RLS) via a tunnel-type PFO associated with hypermobile floppy septum primum (HSP) and prominent Eustachian valve (EV). Of note, a significant enlargement of the aortic root and ascending aorta resulted in a remarkable compression of the right atrial cavity and reduction of the interatrial septum (IAS) length, proportionally increasing its mobility and thus the amount of RLS. Following heart–brain team discussion, transcatheter PFO closure was recommended. After written informed consent, the patient underwent a successful percutaneous PFO closure with a self-expanding double-disk nitinol mesh PFO device (18/24 mm MemoPart) under local anesthesia and mild sedation, with fluoroscopic and rotational intracardiac echocardiography (rICE) guidance using a 9 F–9 MHz Ultra ICE catheter-based ultrasound probe. Two-month follow-up with 2D contrast TTE color Doppler and contrast-enhanced transcranial Doppler (c-TCD) showed correct device position, with no residual shunt.DiscussionEnlargement of the aortic root with increasing age may reorientate horizontally the IAS, allowing part of the flow to stream directly toward the PFO, decrease the size and length of IAS, and proportionally increase its mobility, thus uncovering latent or previously trivial RLSs in older hypertensive patients suffering from ESUS.